2012
DOI: 10.5709/ce.1897-9254.37
|View full text |Cite
|
Sign up to set email alerts
|

Punishment as a Price to Pay

Abstract: Management meted out punishment to enforce rules and encourage adherence. However, the effectiveness depended on how the employees perceive and interpret the policy. Therefore, it was uncertain how to best achieve the target. The paper tested employees' behavioral responses in two conditions, 1) when employees had to pay fines to employer and 2) when employees had to pay fines to co-workers. Condition one was a typical deterrence policy implemented to punish misconduct in an organization, and condition two tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The percentage of employees who are late dropped 66% and 55% of them actually reported to work earlier. It demonstrated that employees who paid fines to their colleague are more successful than paying to their employer in improving their punctuality [23].…”
Section: Punishmentsmentioning
confidence: 99%
“…The percentage of employees who are late dropped 66% and 55% of them actually reported to work earlier. It demonstrated that employees who paid fines to their colleague are more successful than paying to their employer in improving their punctuality [23].…”
Section: Punishmentsmentioning
confidence: 99%
“…Also, it is established in the literature that some people consider the imposition of fine like a price, hence it is likely that the students remain careless even after monetary punishment [Gneezy and Rustichini (2000); Siang (2012)]. For instance, according to Gneezy and Rustichini (2000), when parents are fined for picking up kids late from a day care center; the parents further delayed the arrival time instead of coming on time.…”
mentioning
confidence: 99%
“…For instance, according to Gneezy and Rustichini (2000), when parents are fined for picking up kids late from a day care center; the parents further delayed the arrival time instead of coming on time. Likewise, Siang (2012) shows that imposing fine on employees does not improve the attendance rate as employees consider paying fine like a price for their late coming. Based on this discussion the third hypothesis of the study is:…”
mentioning
confidence: 99%